Levelling the playing field between rural schools and urban schools in a HE context: A Scottish case study. (11th August 2020) - Lasselle, Laurence; Johnson, Mike
Abstract : At a time when interventions in widening access to, and participation in, higher education aim to maximise impact by engaging with schools located in the most deprived communities, school pupils in rural communities, and who experience deprivation, are, in practice, less likely to benefit. Using statistics available from the Scottish government, we show that state secondary schools located in Scottish remote or rural areas are not well served by the indicators capturing socio‐economic, educational, or geographical deprivation widely used in the selection of schools for these outreach interventions. We construct a marker that identifies schools facing higher levels of deprivation than the Scottish average. We argue that (1) this marker is a step in the direction towards levelling the playing field between remote or rural schools and urban schools; and (2) it selects a wider range of schools for outreach interventions.